Enterocutaneous fistulas due to stent migration. How reliable is its use on duodenal benign pathology? a case report - Jimenez Herevia, Aldo Edyair; Hinojosa, Luis Montiel; Ugarte, Diego Hinojosa; Hernandez, Erick Martin Paez; Moreno, Enrique Obregon (International Journal of Research in Medical Sciences, 2020)
Duodenal stenting has been widely used on malignant pathology on selected patients with poor prognosis and advanced disease. In these last years, there has been a clear ampliation of the clinical applications of endoscopy procedures and stents. Its use on benign pathology is spreading but there is a lack of literature about the complications in this context. The incidence of stent migration is about 10-25% in self-expandable metal stent (SEMS), and 2-5% on covered self-expanding metal stents (CSEMS). We reported a clinical case of a 48 years old patient who developed a duodenal ulcer. The patient was submitted to exploratory laparotomy, with duodenal primary closure of the ulcer. Later, the patient developed a enterocutaneous fistula because of the duodenal leak. It was referred to our third level hospital to the hepatopancreatobiliary surgery service. A new exploratory laparotomy with duodenal exclusion was planned, but it was impossible to access due to frozen abdomen. CSEMS was placed in the duodenal bulb resulting in the resolution of leaking, but the stent could not be removed because of migration. The stent trajectory was followed by abdominal x ray and tomography. The patient developed multiple intestinal an fecal enterocutaneous fistulas. It was submitted to multiples endoscopies, colonoscopies and enteroscopy without any success to reaching it. It was decided to perform a right lumbotomy to extract the prothesis. The stent was surgically removed, a planned stoma was left on the right flank on the extraction site.